Experience of Science Teachers in Practicing Rewards System to Increase Students’ Participation in Class - Tolero, Josue A.; Tabile, Delyn O.; Achacoso, Jal M. (Future Science / FSH-PH Publications, 2021)
The study aimed to determine the Experience of Science teachers’ in practicing rewards system to increase student’s participation in class. A qualitative - phenomenology research design was adopted in this study. Interview guide question was used to examine the Experience of Science teachers’ in practicing rewards system to increase student’s participation in class. Data was collected through an interview. Total of 10 teachers were selected as a sample from 8 secondary schools in the Botolan District. The results of this study showed that reward system is effective in the performance of the students and encouragement to give the students good motivation in the learning process. Most of the participant find the rewards system as an effective tool in increasing student’s participation. Recognition such as giving praise and compliments is the usual form of rewards given by the teacher. In addition to extra grades, scores and test or homework exemptions. Preferred rewards of the teachers aside from giving praise and additional grades, are useful rewards such as school supplies, candies, and other food treats. Effective motivation of the student’s in participating in learning activities is the foreseen effects of rewards system.